Does the Entry of Third‐Party Remanufacturers Always Hurt Original Equipment Manufacturers?1. (5th January 2016) - Wu, Xiaole; Zhou, Yu
ABSTRACT: Researchers and managers broadly agree that the entry of third‐party remanufacturers (TPRs) hurts original equipment manufacturers (OEMs) because of the cannibalization problem. Thus, OEMs should always try to deter the entry of TPRs. In this article, we present a contrasting view: Competing OEMs without remanufacturing capacities sometimes benefit from the entry of TPRs. The key feature of our model is that there exists a group of newness‐conscious consumers in the market who do not buy the remanufactured product regardless of the price, whereas a group of functionality‐oriented consumers (FOCs) may buy a remanufactured one at a low price. In a steady‐state‐period setting, we investigate how the number of TPRs affects the OEMs' profits. We find that, from the perspective of two competing OEMs: (i) The entry of one or many TPRs may lead to a higher profit; (ii) The entry of many TPRs may be better than the entry of one TPR; and (iii) The impact of the entry of one or many TPRs may be reversed as FOCs' willingness‐to‐pay for the remanufactured product increases.